ACCOUNTING INFORMATION SYSTEMS AND ENTREPRENEURSHIP: UNDERSTANDING E-COMMERCE - Rifki Abdul Malik; Dendy Syaiful Akbar; Benny Prawiranegara (Asosiasi Dosen Muda Indonesia, 2022)
This information provides an overview of the opportunities for university graduates to find work by region. Waiting for the economic system to create decent jobs may take a long time. One of the other steps that can be taken to create jobs is to encourage entrepreneurship. The purpose of this study is to examine how accounting information systems affect entrepreneurship by including an understanding of e-commerce to strengthen the relationship between the two. This study analyzes primary data from questionnaires distributed to 100 students who have received accounting information systems courses and know and understand e-commerce. The sample selection in this study used a purposive sampling technique. Testing of research variables was carried out using the Partial Least Square method with the SmartPLS application. The results showed that the accounting information system had a significant positive effect on entrepreneurship. E-commerce directly has a significant positive relationship with entrepreneurship. Our analysis shows that knowledge of understanding e-commerce is not able to strengthen accounting information systems' impact on entrepreneurship